Prevalence of Hyponatremia in Patients Presenting with Chronic Liver Disease - Muhammad Haroon Shahid, Muhammad Nadeem, Muhammad Khalid, Shabir Hussain, Samia Yousaf, Komal Iqbal, Imran Ali Syed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A liver illness that worsens over time and affects the liver's ability to function is known as chronic liver disease. Hyponatremia has been linked to higher rates of morbidity and death in cirrhotic patients Objective: To assess the prevalence of Hyponatremia in patients presenting with Chronic Liver Disease Methodology: The current study was cross-sectional, carried out at the department of medicine, Qazi Hussain Ahmad Medical Complex, Nowshera for duration of one year from July 2021 to July 2022. Blood samples of 5ml were taken from all the enrolled patients and sent to the hospital diagnostic laboratory for the examination of sodium level. All the data including demographic details were recorded on a pre-designed Performa. All the data analysis was done by using IBM SPSS version 23. Results: In the current study, the average (SD) level of sodium was 141.96 (11.22) mmol/L. The overall frequency of Hyponatremia was 73 (34.76%) in chronic liver disease patients. Based on the severity of hyponatremia, mild, moderate and severe hyponatremia was observed in 105 (50%), 101 (48.10%) and 4 (1.90%) respectively. Hyponatremia was observed in 18 (23.68%) patients of Child-Pugh class A, in 23 (39.66%) in Child-Pugh class B while hyponatremia was observed in 28 (36.84%) patients of Child-Pugh class C (p˃0.05). Conclusion: Our study concludes that the frequency of hyponatremia in patients of chronic liver disease was high Keywords: Prevalence; Hyponatremia; Chronic Liver Disease